Beetroot (Beta Vulgaris) extraction: the stability of natural colorant and its antioxidant activity - Ahmad Fadzillah, Nurrulhidayah; Muhammad, Nurul Widad Fitri; Othman, Rashidi; Rohman, Abdul; Tukiran, Nur Azira; Hamid, Anis Hamizah (International Institute for Halal research and Training (INHART), 2018)
The natural colorant compound from beetroot obtained from chemical-based extraction was identified as an alternative source of commercial synthetic colorant. In this study, powdered alkaloid compound was treated separately with 1M of hydrochloric acid and 100% ethanol prior to extraction. The compound obtained (betalain) from this method was analyzed in terms of its stability towards different temperature and UVA and UVB light exposure, respectively. The result showed that the absorbance readings were different when exposed to different temperature and light. The color of betalain degrades when treated under extreme temperature. Longer UV exposure time deteriorates the dye. Antioxidant activity of beetroot was also studied using DPPH assays. Result revealed that scavenging activity of beetroot increased proportionally to its concentration with the highest 50% inhibition activity recorded at 77.48%.